Cover, Table of Content and Editorial Team - ATBES, Admint (Advances in Tropical Biodiversity and Environmental Sciences, 2019)
PUBLISHER :  Research Center and Community Service Board, Udayana University. Campus of Bukit Jimbaran, Badung, Bali, Indonesia